Is there a place and role for endocytic TCR signaling?. Issue 1 (12th August 2019) - Saveanu, Loredana; Zucchetti, Andres E.; Evnouchidou, Irini; Ardouin, Laurence; Hivroz, Claire
Abstract: T‐lymphocyte activation relies on the cognate recognition by the TCR of the MHC‐associated peptide ligand (pMHC) presented at the surface of an antigen‐presenting cell (APC). This leads to the dynamic formation of a cognate contact between the T lymphocyte and the APC: the immune synapse (IS). Engagement of the TCR by the pMHC in the synaptic zone induces a cascade of signaling events leading to phosphorylation and dephosphorylation of proteins and lipids, which ultimately shapes the response of T lymphocytes. Although the engagement of the T‐cell receptor (TCR) takes place at the plasma membrane, the TCR/CD3 complexes and the signaling molecules involved in transduction of the TCR signal are also present in intracellular membrane pools. These pools, which are both endocytic and exocytic, have tentatively been characterized by several groups including ours. We will herein summarize what is known on the intracellular pools of TCR signaling components. We will discuss their origin and the mechanisms involved in their mobility at the IS. Finally, we will propose several hypotheses concerning the functional role(s) that these intracellular pools might play in T‐cell activation. We will also discuss the tools that could be used to test these hypotheses.